Keanekaragaman, Kelimpahan, dan Sebaran Kopepoda (Krustasea) di Perairan Bakau Segara Anakan, Cilacap - Mulyadi; Dewi Citra Murniati, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Diversity, Abundance, and Distribution of Copepods (Crustacea) in the Mangrove Area of Segara Anakan, Cilacap. Observations on the diversity of Copepods, its abundance, and its distribution in three mangrove and estuarine locations in Segara Anakan Lagoon, Cilacap, were conducted in May (dry season) and November (rainy season) 2009. This study aims to determine the relationship of diversity and abundance of Copepods with some environmental factors that affect its distribution in the dry and rainy seasons. Copepod samples were taken from Kutawaru waters, Dermaga Sleko, and Ciperet using vertical and horizontal plankton nets, day and night. They were then preserved, deposited, and identified in MZB LIPI. There were 36 species of Copepods from 18 genera and 20 families, including 10 new records. The highest species diversity of Copepods was recorded in November, while the lowest was in May. The average abundance in May was higher than in November. The diversity and abundance in Ciperet in both dry and rainy seasons were always higher than the other two sites. Acartia erythraea, A. sinjiensis and Pseudodiaptomus annandalei were found to dominate the waters especially during the dry season in May. The community composition of Copepods occupying the waters was determined by salinity, while its activity and development were determined by temperature.